Defamation law and social attitudes : ordinary unreasonable people - Baker, Roy. (Cheltenham, U.K. : Edward Elgar, 2011)
'The common law determines whether a publication is defamatory by considering how'ordinary reasonable people' would respond to it. But how does the law work in practice? Who are these'ordinary reasonable people' and what do they think? This book examines the psychology behind how judges, juries and lawyers decide what is defamatory. Drawing on a thorough examination of case law, as well as extensive empirical research, including surveys involving over 4,000 members of the general public, interviews with judges and legal practitioners and focus groups representing various sections of the community, this book concludes that the law reflects fundamental misperceptions about what people think and how they are influenced by the media. The result is that the law tends to operate so as to unfairly disadvantage publishers, thus contributing to defamation law's infamous'chilling effect' on free speech'--Provided by publisher.
Introduction -- Formulating the test for defamation -- Refining the test -- Applying the test -- The lawyers' answers -- The publics' answers -- The third-person effect -- Accomodating the third-person effect -- Conclusion -- Appendix I. Description of the imaginary media reports as given to intreviewees -- Appendix II. Text of hypothetical newspaper article and interpretations used in student (denotative meaning) survey.
Includes bibliographical references (p. 323-332) and index.
Keywords: Libel and slander -- Australia; Libel and slander -- Australia -- Public opinion; Public opinion -- Australia